2021
DOI: 10.1111/nan.12736
|View full text |Cite
|
Sign up to set email alerts
|

Balloon cells promote immune system activation in focal cortical dysplasia type 2b

Abstract: Aims Focal cortical dysplasia (FCD) type 2 is an epileptogenic malformation of the neocortex associated with somatic mutations in the mammalian target of rapamycin (mTOR) pathway. Histopathologically, FCD 2 is subdivided into FCD 2a and FCD 2b, the only discriminator being the presence of balloon cells (BCs) in FCD 2b. While pro‐epileptogenic immune system activation and inflammatory responses are commonly detected in both subtypes, it is unknown what contextual role BCs play. Methods The present study employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…These data further support the notion that an activation of inflammatory molecules is an intrinsic specific feature of this type of FCD and is not triggered by chronic seizure activity per se [29]. The discrepancy between the two FCD subtypes, with stronger expression of complement components in Type IIb than in IIa, also observed in a previous paper [34], is not an unexpected finding because they are different in several clinical, radiological, postsurgical outcome [35], and morphological aspects [29]. As suggested by Zimmer et al [34], BCs, the immature abnormal cells only present in Type IIb FCD, may be crucial driver of inflammation and partly explain the less severe alterations noted in IIa FCD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These data further support the notion that an activation of inflammatory molecules is an intrinsic specific feature of this type of FCD and is not triggered by chronic seizure activity per se [29]. The discrepancy between the two FCD subtypes, with stronger expression of complement components in Type IIb than in IIa, also observed in a previous paper [34], is not an unexpected finding because they are different in several clinical, radiological, postsurgical outcome [35], and morphological aspects [29]. As suggested by Zimmer et al [34], BCs, the immature abnormal cells only present in Type IIb FCD, may be crucial driver of inflammation and partly explain the less severe alterations noted in IIa FCD.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of an upregulation of the classical complement pathway in human epileptic tissues, and particularly in Type IIb FCD, is supported by several other studies performed on postsurgical brain tissue [23,24,33,34]. Immunohistochemical data frequently report high level of complement proteins in astrocytes and in the abnormal DNs and BCs.…”
Section: Discussionmentioning
confidence: 70%
“…Focal Cortical Dysplasia (FCD): Some FCD produce an activation of cerebral innate immunity, mainly microglial activation. Although their exact pathogenesis remains poorly understood, somatic mutations in the mTOR pathway have been found in FCD type IIb [72].…”
Section: Hippocampal Sclerosis (Hs)mentioning
confidence: 99%
“…On the other hand, it is known that the generation and recurrence of seizures have widespread consequences on whole brain homeostasis and the onset of a “vicious cycle” of neuroinflammation is likely one of the most important factors contributing to the consolidation of the epileptogenic mechanisms [ 17 ]. In the specific case of FCD type II, recent evidence supports the hypothesis that factors contributing to the maintenance of the pro-inflammatory drive in this condition include the up-regulation of inflammatory mediators in dysmorphic cells [ 18 ], imbalance of cytokines’ regulatory networks [ 19 ] and the pro-inflammatory potential of the seizures themselves [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we have previously shown that IL-1β can decrease GABA currents amplitude in human drug-resistant temporal lobe epilepsy (TLE) by activation of IL-1β signaling [ 22 ]. Here, we investigated the effect of IL-1β on GABAergic neurotransmission in pediatric brain tissues from patients affected by FCD IIb, which is the most severe form of FCD considering the high level of neuroinflammation [ 18 ]. Indeed, even though several reports supporting the role of this cytokine in neurodevelopmental epilepsies have already been published [ 23 , 24 ], there is still scarce evidence regarding its potential role in the “plastic” neurotransmission that characterizes neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%